Elaboración y Aplicación de un Antígeno Parasitario (Cooperia curticei) en Ovinos. - Cuascota Zambonino, Alexandra Isabel (2022)
Gastrointestinal parasites in ovines represent one of the sanitary problems in the production worldwide. Gastrointestinal parasites affect the health of ovine, causing diarrhea, loss of appetite and anemia, which can lead to the death of the animal. A study was carried out in the Cusualo neighborhood of the Zumbahua parish of the Pujilí canton on a population of 30 creole breed ovines between the ages of 0 - 3 years, of which 14 are females and 16 are males. Coproparasitic, immunological and hematological examinations were performed on each of the animals participating in the study in order to determine the presence of Cooperia curticei and to determine the health status of the animals. An analysis of variance (ANOVA) with a randomized design was developed. A 100% presence of Cooperia curticei was obtained with no significant difference between age and gender to which the animal belongs; hematology showed 100% eosinophilia in the total population, related to the parasitosis presented by the animal, 10% of the animals presented anemia between the ages of 8 and 9 months, all males and each of them presented different types of anemia such as: normocytic hyperchromic, macrocytic normochromic and macrocytic hyperchromic; 6.66% had a presence of lymphocytosis which is related to an inflammatory process or a chronic course infection, 10% of the population presented leukocytosis which is related by an infection or inflammation; 23.33%, being a high value, is related to the release of epinephrine, which is presented by fear, excitement or stress. Leukocytosis and lymphocytosis were present in 10% of the population, which is presented by the presence of an infection and by the stress to which they were subjected in the extraction of the sample. 3.33% of the population showed elevated values for leukocytosis, lymphocytosis and neutrophilia which are responsible for the reaction to parasites and stress. For lymphopenia and neutrophilia 16.66%, which is related to stress neutrophilia. The 6.66% gave high values for leukocytosis and neutrophilia, which is presented by the presence of viral, bacterial or parasitic infection and stress. In the immunological reaction, 43% of positive humoral presence for IgE was obtained, which indicates a condition related to the presence of parasitosis in the animals submitted to the study. In conclusion, it was possible to determine the presence of Cooperia curticei in the Zumbahua parish in creole breed ovines without distinction of age and gender with an immunological reaction.